2015
DOI: 10.1016/j.drugalcdep.2015.01.016
|View full text |Cite
|
Sign up to set email alerts
|

A population-based Swedish Twin and Sibling Study of cannabis, stimulant and sedative abuse in men

Abstract: Background Prior studies, utilizing interview-based assessments, suggest that most of the genetic risk factors for drug abuse (DA) are non-specific with a minority acting specifically on risk for abuse of particular psychoactive substance classes. We seek to replicate these findings using objective national registry data. Methods We examined abuse of cannabis, stimulants (including cocaine) and sedatives ascertained from national Swedish registers in male–male monozygotic (1720 pairs) and dizygotic twins (12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 26 publications
(41 reference statements)
0
23
0
Order By: Relevance
“…Patterns of cannabis use such as lifetime cannabis use (never/ever used) and Cannabis Use Disorder (CUD) are influenced by genetic factors 9,10 . Twin heritability reaches 45% for lifetime cannabis use and 51% to 70% for CUD 11,12 . Genome wide Association Studies (GWAS) have also shown a significant genetic correlation between lifetime cannabis use and CUD on the one hand, and schizophrenia on the other 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Patterns of cannabis use such as lifetime cannabis use (never/ever used) and Cannabis Use Disorder (CUD) are influenced by genetic factors 9,10 . Twin heritability reaches 45% for lifetime cannabis use and 51% to 70% for CUD 11,12 . Genome wide Association Studies (GWAS) have also shown a significant genetic correlation between lifetime cannabis use and CUD on the one hand, and schizophrenia on the other 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Cannabis use is increasing in the population [4][5][6] and among users around 9% become dependent 7 . The genetic risk component is high with heritability estimates of 51 8 -70% 9 . Here we report the first genome-wide significant risk locus for cannabis use disorder (CUD, P=9.31x10 -12 ) that replicates in an independent population (P replication =3.27x10 -3 , P metaanalysis =9.09x10 -12 ) based on genome-wide association study (GWAS) of 2,387 cases and 48,985 controls followed by replication in 5,501 cases and 301,041 controls.…”
Section: Introductory Paragraphmentioning
confidence: 99%
“…Previous studies in non-psychotic populations (Kendler & Prescott, 1998;Kendler et al 2000Kendler et al , 2015 highlight that a combination of genetic and environmental factors influence cannabis use. Patients with psychosis are more likely to use cannabis than the general population (D 'Souza, 2007) but psychosis-prone individuals are not more likely to use cannabis (Henquet et al 2005).…”
Section: Introductionmentioning
confidence: 99%